First Board of Trustees (Institutional Knowledge at Singapore Management University, 2000)
Singapore President S R Nathan hosts a reception for Singapore Management University’s first board of trustees and senior management on 15 March 2000. Pictured on the steps of the Istana, front row, left to right: Trustee Kuok Khoon Ean, Trustee Victor Fung; Chairman Ho Kwon Ping; Singapore President S R Nathan; SMU President Janice Bellace and Trustee Han Cheng Fong. Middle row: Dean Tsui Kai Chong; Provost Tan Chin Tiong, Trustee Fang Ai Lian, Trustee Gan See Khem, Trustee Seah Jiak Choo, Deputy President Tan Teck Meng, Deputy Dean Low Kee Yang. Back row: Trustee Latiff Bin Ibrahim, Trustee Loo Choon Yon, Trustee John Niland, Trustee Jaspal Singh, Trustee Ong Keng Yong, Trustee Sunil Sreenivasan.